Firn Meltwater Retention on the Greenland Ice Sheet: A Model Comparison - Steger, Christian R.; Reijmer, Carleen H.; van den Broeke, Michiel R.; Wever, Nander; Forster, Richard R.; Koenig, Lora S.; Kuipers Munneke, Peter; Lehning, Michael; Lhermitte, Stef; Ligtenberg, Stefan R. M.; Miège, Clément; Noël, Brice P. Y. (Frontiers in Earth Science, 2017)
Runoff has recently become the main source of mass loss from the Greenland Ice Sheet and is an important contributor to global sea level rise. Linking runoff to surface meltwater production is complex, as meltwater can be retained within the firn by refreezing or perennial liquid water storage. To constrain these uncertainties, the outputs of two offline snow/firn models of different complexity (IMAU-FDM and SNOWPACK) are compared to assess the sensitivity of meltwater retention to the model formulation (e.g., densification, irreducible water content, vertical resolution). Results indicate that model differences are largest in areas where firn aquifers form, i.e., particularly along the south-eastern margin of the ice sheet. The IMAU-FDM simulates higher densification rates for such climatic conditions and prescribes a lower irreducible water content than SNOWPACK. As a result, the model predicts substantially lower amounts of refreezing and liquid water storage. SNOWPACK performs better for this area, confirmed both by density profiles from firn cores and radar-inferred observations. Refreezing integrated over the entire ice sheet and averaged for the period 1960 - 2014 amounts to 216 Gt a-1 (IMAU-FDM) and 242 Gt a-1 (SNOWPACK), which is 41% and 46% of the total liquid water input (snowmelt and rainfall). The mean areal extents of perennial firn aquifers for 2010 - 2014 simulated by the models are 55,700 km2 (IMAU-FDM) and 90,200 km2 (SNOWPACK). Discrepancies between modeled firn profiles and observations emphasize the importance of processes currently not accounted for in most snow/firn models, such as vertical heterogeneous percolation, ponding of water on impermeable layers, lateral (sub-)surface water flow, and the issue of ill-constrained refreezing conditions at the base of firn aquifers.